Sonority effects in the production of the triconsonantal sequences Ct/d]σC by Brazilian learners of L2 English - Reis, Felipe Santos dos; Lucena, Rubens Marques de (Cadernos do IL, 2020)
This study investigates the production of a variable pattern in English by Brazilian L2 learners, i.e. triconsonantal sequences containing coronal plosives flanked by heterosyllabic consonants. Thus, the interlanguage of 24 learners from the city of Campina Grande in the state of Paraíba, Brazil, is analyzed to achieve the following objectives: (1) verify the phonological processes whereby the sequences Ct/d]σC are simplified in the participants’ interlanguage; and (2) examine the role of sonority in the surface phonetic representations of these sequences. 1,071 tokens were audio-recorded, coded and subjected to multivariate analysis using Rbrul (JOHNSON, 2015). The results indicate that sonority-based principles play an important role in the application of repair strategies on the surface forms of these complex structures.